Investigating the Structural Shift in Indonesia’s Energy Consumption and its Implications for Sustainable Development and Energy Policy - Noviar, Helmi; Saputra, Jumadil; Intyas, Candra Adi; Arip, Mohammad Affendy; Wakimin, Nur Fadzlunnisaa (International Journal of Energy Economics and Policy, 2025)
The path of economic development and the standard of living of households are determined by the availability of energy as a production factor. Patterns of final energy use in Indonesia have exhibited notable structural change between 2010 and 2023. The purpose of this research is to examine the dynamics of the shift in energy consumption from the household sector to the productive sector, specifically, industry and transportation, and its consequences for sustainable development and energy security. The Indonesian Energy Balance (2010-2023) was obtained from Central Bureau of Statistics (BPS), International Energy Agency (IEA), and other relevant publications, which are the sources of secondary data used in the research methodology. Using a time series technique, the analysis compared the pre-, during, and post-COVID-19 pandemic phases to determine the proportion of energy consumption for each sector. To ensure uniformity across energy sources, all data were converted to barrels of oil equivalent (BOE). With average growth rates of 7.66% and 6.11% per year, respectively, the data reveal that the transportation and industrial sectors are the primary drivers of growth in the nation’s energy consumption. On the other hand, the household sector saw a notable decline (–1.56), consistent with the switch from biomass to electricity and LPG. There were steady but modest increases in the public, commercial, and agricultural sectors. Although industry and transportation once again drove the post-pandemic recovery, the COVID-19 pandemic turned out to be a turning point that curtailed productive energy use. These results support the notion that Indonesia’s energy use is shifting increasingly toward the productive sector as the country’s economy becomes more sophisticated and industrialized. However, the Net Zero Emission 2060 target is seriously threatened by the prevalence of fossil fuels in the industrial and transportation sectors. Therefore, to maintain a balance between environmental sustainability, social justice, and growth, future energy policy must prioritize efficiency, diversity, and accelerating the transition to clean energy.